Penahanan Ijazah Pekerja Oleh Perusahaan Dalam Perjanjian Kerja Berdasarkan Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan (Studi Putusan Nomor: 205/Pdt.G/2019/PN.SDA) - Daryanto Wibowo; Abdullah Sulaiman (JOURNAL of LEGAL RESEARCH, 2020)
This study aims to explain the legal provisions for the detention of workers' certificates in the work agreement and legal protection for workers who suffer losses due to having their certificates detained by the company. The company requires workers to submit an original certificate to the company so that workers can be bound by the regulations set by the company. These bound workers cannot and do not have the freedom to leave the company for a certain period of time on the work contract proposed by the company and must be fulfilled. The detention of a certificate in a work agreement is not regulated by the prevailing laws and regulations and tends to harm workers and violate workers' human rights. This research is normative juridical by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results showed that the detention of workers' certificates was not regulated in the labor-related legislation, meaning that there was a legal vacuum. Due to the legal vacuum that occurs, employers carry out the act of detaining the certificate based on habits and agreements and freedom of contract in the agreement as the source of law.Keywords: Diploma Detention, Work Agreement, Labor Law, Losses, Illegal Acts